2019
DOI: 10.3390/metabo9070148
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Staphylococcus aureus Elicits the Production of Host Very Long-Chain Saturated Fatty Acids with Antimicrobial Activity

Abstract: As a facultative intracellular pathogen, Staphylococcus aureus is able to invade and proliferate within many types of mammalian cells. Intracellular bacterial replication relies on host nutrient supplies and, therefore, cell metabolism is closely bound to intracellular infection. Here, we investigated how S. aureus invasion affects the host membrane-bound fatty acids. We quantified the relative levels of fatty acids and their labelling pattern after intracellular infection by gas chromatography-mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Additionally, innate immune system in epithelial cell and in abscesses Fig. 6 Semi-quantitative RT-PCR of mecA and the fatty acid synthetic operon take advantage of long chain free fatty acids such as linoleic acid [C18:2 (n-6,9)], oleic acid [C18:1 (n-9)] and palmitoleic acid [C16:1 (n-7)], which are unsaturated fatty acids and saturated palmitic acid (C16:0) and stearic acid (C18:0) (Bravo-Santano et al 2019b;Kenny et al 2009). These major long chain fatty acids are considered bactericidal or bacteriostatic depending on their structural characteristics and they induce stress response of S.aureus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, innate immune system in epithelial cell and in abscesses Fig. 6 Semi-quantitative RT-PCR of mecA and the fatty acid synthetic operon take advantage of long chain free fatty acids such as linoleic acid [C18:2 (n-6,9)], oleic acid [C18:1 (n-9)] and palmitoleic acid [C16:1 (n-7)], which are unsaturated fatty acids and saturated palmitic acid (C16:0) and stearic acid (C18:0) (Bravo-Santano et al 2019b;Kenny et al 2009). These major long chain fatty acids are considered bactericidal or bacteriostatic depending on their structural characteristics and they induce stress response of S.aureus.…”
Section: Discussionmentioning
confidence: 99%
“…However, hexadecenoic acid (C16:0), octadecanoic acid (C18:0) and eicosanoic acid (C20:0) could reduce biofilm formation in this study. This might be from the different culture condition including medium, bacterial strain and dose-dependent supplementation of fatty acid (Bravo-Santano et al 2019a;Lade et al 2019;Yoon et al 2018). As a conclusion, this phenomenon might explain how the Δagr mutant strain retained a lower level of fatty acid in the supernatant, since maintaining higher levels of fatty acids would interfere with biofilm formation and increase the instability of the cytoplasmic membrane leading to higher antibiotic susceptibility.…”
Section: Influence Of the Exogenous Addition Of Fatty Acids On Antibimentioning
confidence: 98%
“…However, hexadecenoic acid (C16:0), octadecanoic acid (C18:0) and eicosanoic acid (C20:0) could reduce biofilm formation in this study. This might be from the different culture condition including medium, bacterial strain and dose-dependent supplementation of fatty acid (Bravo-Santano et al 2019a;Lade et al 2019;Yoon et al 2018). As a conclusion, this phenomenon might explain how the Δagr mutant strain retained a lower level of fatty acid in the supernatant, since maintaining higher levels of fatty acids would interfere with biofilm formation and increase the instability of the cytoplasmic membrane leading to higher antibiotic susceptibility.…”
Section: Influence Of the Exogenous Addition Of Fatty Acids On Antibimentioning
confidence: 99%
“…It has been reported that C20:0 does not show a significant decrease in biofilm formation, especially at low concentration [33]. However, inhibition has been reported to be dose-dependent [34][35][36].…”
Section: Phage Xccϕ1 Hydroxyapatite and Eicosanoic Acid Modulate XCmentioning
confidence: 97%